2012
DOI: 10.1007/s00232-012-9512-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Contrast Media on Oxidative Stress, Ca2+ Signaling and Apoptosis in Kidney

Abstract: Contrast media (CM)-induced nephropathy is a common cause of iatrogenic acute renal failure. The aim of the present review was to discuss the mechanisms and risk factors of CM, to summarize the controlled studies evaluating measures for prevention and to conclude with evidence-based strategies for prevention. A review of the relevant literature and results from recent clinical studies as well as critical analyses of published systematic reviews used MEDLINE and the Science Citation Index. The cytotoxicity indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 72 publications
0
31
0
2
Order By: Relevance
“…In several studies, tubular necrosis and epithelial damage were shown to be major indicators in nephrotoxicity damage (Naziroglu et al, 2013). In studies seeking to identify the tubular epithelial injury, tubular necrosis, hyaline casts, and haemorrhagic casts were investigated (Droguett et al, 2014).…”
Section: Page 12 Of 34mentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, tubular necrosis and epithelial damage were shown to be major indicators in nephrotoxicity damage (Naziroglu et al, 2013). In studies seeking to identify the tubular epithelial injury, tubular necrosis, hyaline casts, and haemorrhagic casts were investigated (Droguett et al, 2014).…”
Section: Page 12 Of 34mentioning
confidence: 99%
“…It has been reported that pro-inflammatory mediators, such as TNF-α, IL-1β, and TGF-1β, are produced in acute I/R injury due to tubular and endothelial cellular damage, and these inflammatory cytokines contribute to the enhancement of renal injury (Bonventre, 2004). In CM-induced renal injury, tubular and endothelial cellular damage are observed, similar to other renal injuries (Naziroglu et al, 2013). Anti-cytokine treatment has been tried experimentally for renal injuries caused by nephrotoxic substances and has been shown to potentially decrease the severity of renal injury (Di Paola et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Under many kinds of cellular stresses, unfolded proteins are accumulated in the ER and influence normal ER functions [10,11]. Activation of caspase-12 plays a role in the triggering of apoptosis by the intrinsic ER stress apoptotic pathway, which is mediated by ER through activation of the caspase-9-and caspase-3-dependent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, tubular necrosis and epithelial injury have been shown to be significant indicators in nephrotoxicity injury; 53 tubular epithelial damage, tubular necrosis, hyaline and haemorrhagic casts have been found in these investigations. 54 In the development of nephropathy, significant damage to haemorrhagic renal tubules with hyaline occurs and is related to tubular injury.…”
Section: Discussionmentioning
confidence: 75%